Potential contribution of the gut microbiota to the development of portal vein thrombosis in liver cirrhosis - Huang, Xin-yu; Zhang, Ying-hui; Yi, Shi-yu; Lei, Lei; Ma, Tao; Huang, Rui; Yang, Lan; Li, Zhen-mao; Zhang, Di (Frontiers in Microbiology, 2023)
Background Portal vein thrombosis (PVT) is a serious complication of liver cirrhosis (LC) and is closely related to gut homeostasis. The study aimed to investigate the composition of gut microbiota and its putative role in PVT development in LC. Methods 33 patients with LC admitted between January 2022 and December 2022 were enrolled in this study. Based on imaging findings, they were categorized into LC without PVT (n = 21) and LC with PVT (n = 12) groups. Fecal samples were collected from each participant and underwent 16S rDNA sequencing. Results D-Dimer and platelet elevations were the main clinical features of LC with PVT. The alpha and beta diversity of the gut microbiota in LC with PVT group was found to be significantly higher compared to the control group. The structure of the gut microbiota was significantly different between the two groups. Based on LEfSe data, the genera Akkermansia, Eubacterium hallii group, Fusicatenibacter, and Anaerostipes were enriched in the LC with PVT, while Enterococcus, Weissella, Bacteroides, and Subdoligranulum were enriched in those of the LC subjects. Changes in microbiota structure result in significant differences in gut microbiota metabolism between the two groups. Altered levels of the microbiota genera were shown to be correlated with coagulation factor parameters. In animal experiments, the addition of Bacteroides reversed the CCl4-induced PVT. Conclusion Liver cirrhosis with PVT led to a disorder in the gut microbiota, which was characterized by an increase in pathogenic bacteria and a decrease in beneficial bacteria. Furthermore, modulating the gut microbiota, especially Bacteroides, may be a promising therapeutic approach to reduce the progression of PVT in LC.